AEROBIC AND ANAEROBIC AMMONIUM OXIDISING BACTERIA ENRICHMENT FROM MINED MUNICIPAL SOLID WASTE IN SHARONANAMMOX PROCESS - S., Sri Shalini; Joseph., Kurian (Malaysian Journal of Science, 2014)
Ammoniacal nitrogen removal by novel processes like Single reactor system for high activity ammonia removal over nitrite (SHARON) and Anaerobic ammonium oxidation (ANAMMOX) processes are currently considered as advantageous than conventional processes. It requires aerobic ammonium oxidising bacteria (AOB) and anaerobic ammonium oxidising bacteria (AnAOB) to conduct the SHARON and ANAMMOX processes. This paper presents the feasibility of enriching the AOB and AnAOB using mined municipal solid waste (MSW) in batch reactors for a period of 37 days. In AOB reactor with nitrogen loading of 0.5 kg N/d showed Partial Nitritation Efficiency of 82.6% with 3.8 Ã— 108 MPN/100mL of AOB population obtained. AnAOB reactor enriched with anammox biomass efficiently removed 78% of ammonia with the specific anammox activity reached up to 0.10 mg NH4-N/mg MLVSS/d. The nitrogen transformations along with the formation of intermediates (hydrazine and hydroxylamine), biomass development, free ammonia and free nitrous acid concentrations in the batch reactors confirmed the enrichment AOB and AnAOB biomass activity using mined MSW. (Keywords: Mined municipal solid waste, ammoniacal nitrogen removal, aerobic ammonium oxidising bacteria and anammox)